A comparative - descriptive survey of the determinants of comfort in higher education classroom chair seating - Carandang, Kryztle Veronica C.; Florendo, Raquel Baltazar (2010.)
ABSTRACT This comparative-descriptive survey identified the determinants of comfort in higher education classroom chair seating. It determined the type of classroom chair favored by the students, and the determinant of comfort influential in this choice. A purposive type of sampling considering respondents' differences in gender, age, and body types was utilized. Five typical classroom chairs in the UP Diliman College of Home Economics were assessed by thirty-five (35) college students through sensory and experiential types of evaluation. The chairs assessed all have a seat, four legs, a back, and a writing tablet. Material categories of chairs used were wooden, plastic, and combination of wood and metal, and plastic and metal. The following were factors identified with the determinants of for classroom chairs: (1) visual, (2) tactile, (3) auditory, (4) olfactory, (5) anthropometric, (6) ergonomic, and (7) somatic attributes. A comparison of the functional relationships among the chair and the attributes allowed the researcher to arrive at trends. Results show that the seven attributes were considered in the perception of a comfortable chair. Anthropometric and ergonomic attributes dependent of the students' body type were considered greatly, making the wooden chairs fitting for these attributes. The visual attribute dependent on the general form and material composition was most influential in the determining the most comfortable chair, which was the smooth-textured modern plastic chair in metal frames and legs. This study provided insights for the identification of factors determining comfort in higher education classroom chairs. It also provided a reference for the College of Home Economics the most effective classroom chair seating.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Chairs -- Philippines